2023
DOI: 10.1091/mbc.e22-09-0442
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the roles of cell shape and Fat and Dachsous planar polarity in arranging the Drosophila apical microtubule network through quantitative image analysis

Abstract: In epithelial cells, planar polarisation of subapical microtubule networks is thought to be important for both breaking cellular symmetry and maintaining the resulting cellular polarity. Studies in the Drosophila pupal wing and other tissues have suggested two alternative mechanisms for specifying network polarity. On one hand mechanical strain and/or cell shape have been implicated as key determinants, on the other the Fat-Dachsous planar polarity pathway has been suggested to be the primary polarising cue. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
(160 reference statements)
1
1
0
Order By: Relevance
“…A Previous work on core pathway complexes (Fz6/Vangl2/ Celsr1) in the epidermis has shown that TEC is used for quickly remodeling cell boundaries during cell divisions (23). Previous works and the current work, in both Drosophila and mammalian cell culture, show that Ft/Ds and Fat4/Dchs1 boundary complexes are extremely stable (16,(24)(25). We therefore suggest that TEC in the Fat4/Dchs1 system may also be important for plasticity and remodeling of cell boundaries in different conditions, as it allows removing highly stable complexes in a very efficient manner.…”
Section: Discussionsupporting
confidence: 62%
“…A Previous work on core pathway complexes (Fz6/Vangl2/ Celsr1) in the epidermis has shown that TEC is used for quickly remodeling cell boundaries during cell divisions (23). Previous works and the current work, in both Drosophila and mammalian cell culture, show that Ft/Ds and Fat4/Dchs1 boundary complexes are extremely stable (16,(24)(25). We therefore suggest that TEC in the Fat4/Dchs1 system may also be important for plasticity and remodeling of cell boundaries in different conditions, as it allows removing highly stable complexes in a very efficient manner.…”
Section: Discussionsupporting
confidence: 62%
“…But some key published data were questioned when reexamined and the model challenged by new observations on microtubules in polarized larval and adult abdominal cells [ 34 ]. Microtubule organization is nevertheless related to cell shape in several different kinds of epidermis [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%